A maximum likelihood estimation framework for delay logistic differential equation model - Mahmoud, A.A. (American Institute of Physics Inc., 2016)
This paper will introduce the maximum likelihood method of estimation for delay differential equation model governed by unknown delay and other parameters of interest followed by a numerical solver approach. As an example we consider the delayed logistic differential equation. A grid based estimation framework is proposed. Our methodology estimates correctly the delay parameter as well as the initial starting value of the dynamical system based on simulation data. The computations have been carried out with help of mathematical software: MATLABÂ® 8.0 R2012b. Â© 2016 Author(s).